On Semi-p-Proper Mappings - Dawood, Narjis. A.U. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The aim of this paper is to introduce a new type of proper mappings called semi-p-proper mapping by using semi-p-open sets, which is weaker than the proper mapping. Some properties and characterizations of this type of mappings are given.